Effect of Rumensin on performance of finishing steers - Fink, G.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Two hundred ten Hereford x Angus crossbred yearling steers were used in two trials to determine effects of Monensin (trade name Rumensin) on performance and carcass characteristics. Top dressing a protein supplement (crumbles or pellets) containing Rumensin was an acceptable way to feed the compound in trial 1. Rumensin increased gain 2.0% reduced feed intake 4.3%, and improved feed efficiency 6.1%. Trial 2 was conducted to determine if Rumensin could be fed to steers after they had been on a high concentrate ration at least 56 days. Four levels (1, 10, 20, and 30 grams per ton) were compared. Ten or 20 grams per ton was most beneficial the final 63 days in the feedlot after a preliminary feeding period of 56 days without Rumensin.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Rumensin; Performance; Steers